The Integration of Knowledge in Islam and a Critique of Western-Style Fragmentation of Knowledge: A Study of the Ideas of Ziauddin Sardar and Imre Lakatos - Amin, Fajar; Khakim, Usmanul (Islamic Journal of Communication and Public Discourse, 2026)
Background: Modern civilization is built upon a secular and fragmented epistemology that separates rationality from spiritual values a condition Ziauddin Sardar refers to as epistemic apartheid. This worldview has significantly influenced educational systems in many Muslim countries, including Indonesia, leading to a dichotomy between religious and worldly sciences. Objective: This study aims to explore the epistemological roots of this fragmentation from both Islamic and Western perspectives and to examine the potential for synthesizing the ideas of Sardar and Imre Lakatos. Method: The research adopts a qualitative library research approach utilizing a philosophical-analytical method. It traces the historical and epistemological dimensions of knowledge fragmentation and comparatively analyzes Sardar’s Islamic epistemological reconstruction and Lakatos’s scientific research programmes model. Findings and Implications: Sardar advocates for knowledge reconstruction based on the Islamic worldview, the principle of tawḥīd, and the objectives of maqāṣid al-sharīʿah, ensuring that knowledge remains value-driven and oriented toward the public good. Lakatos offers a structural model of scientific progress comprising a hard core and protective belt, which maintains theoretical continuity while accommodating rational development. Both thinkers reject positivism and value neutrality, emphasizing that knowledge is shaped by foundational assumptions and must respond to real ethical and social challenges. The proposed synthesis results in a comprehensive paradigm encompassing ontological (tawḥīd), epistemological (revelation, reason, and experience), axiological (maqāṣid), and methodological (research programmes) dimensions. Conclusion: The integrated framework offers a practical and transformative proposal for developing a contemporary Islamic epistemology that is rational, ethical, contextual, and capable of guiding future research and educational reform.